(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines the role of moral education lessons in developing national and intercultural competences among primary school pupils. With globalization influencing education, there is an urgent need to balance the preservation of national identity with the acquisition of intercultural skills. Using a qualitative research design, this study investigates the effectiveness of didactic tools such as storytelling, project-based learning, and classroom discussions in fostering both national awareness and respect for cultural diversity. Findings indicate that moral education lessons significantly contribute to strengthening pupils’ understanding of cultural heritage while simultaneously promoting openness towards other cultures. The paper also discusses theoretical frameworks of competence development, reviews international research, and highlights pedagogical strategies that can be integrated into national curricula. Recommendations are provided for teachers, policymakers, and curriculum developers to systematically embed competence-based approaches in early education. The study concludes that moral education, when supported with innovative didactic methods, plays a vital role in shaping responsible, tolerant, and globally competent citizens.